The shifting of secondary inorganic aerosol formation mechanisms during haze aggravation: the decisive role of aerosol liquid water - F. Xie; F. Xie; Y. Su; Y. Su; Y. Tian; Y. Shi; X. Zhou; P. Wang; R. Yu; W. Wang; J. He; J. He; et al. (Atmospheric Chemistry and Physics, 2023)
Although many considerable efforts have been done to reveal the driving factors on haze aggravation, however, the roles of aerosol liquid water (ALW) in secondary inorganic aerosol (SIA) formation were mainly focused on the condition of aerosol liquid water content (ALWC) < 100 µg m−3. Based on the in situ high-resolution field observations, this work studied the decisive roles and the shifting of secondary inorganic aerosol formation mechanisms during haze aggravation, revealing the different roles of ALWC on a broader scale (∼500 µg m−3) in nitrate and sulfate formation induced by aqueous chemistry in the ammonia-rich atmosphere. The results showed that chemical domains of perturbation gas limiting the generation of secondary particulate matter presented obvious shifts from a HNO3-sensitive to a HNO3- and NH3-co-sensitive regime with the haze aggravation, indicating the powerful driving effects of ammonia in the ammonia-rich atmosphere. When ALWC < 75 µg m−3, the sulfate generation was preferentially triggered by the high ammonia utilization and then accelerated by nitrogen oxide oxidation from clean to moderate pollution stages, characterized by nitrogen oxidation ratio (NOR) < 0.3, sulfur oxidation ratio (SOR) < 0.4, ammonia transition ratio (NTR) < 0.7 and the moral ratio of <msubsup>NO3-</msubsup>/<msubsup>SO42-</msubsup>=2:1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="90pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="4f934f2b78299b885908646ed902d934"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-2365-2023-ie00001.svg" width="90pt" height="17pt" src="acp-23-2365-2023-ie00001.png"/></svg:svg>. When ALWC > 75 µg m−3, the aqueous-phase chemistry reaction of SO2 and NH3 in ALW became the prerequisite for SIA formation driven by Henry's law in the ammonia-rich atmosphere during heavy and serious stages, characterized by high SOR (0.5–0.9), NOR (0.3–0.5) and NTR (>0.7), as well as the high moral ratio of <msubsup>NO3-</msubsup>/<msubsup>SO42-</msubsup>=1:1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="90pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="a4275230ebd894edd1a417cc5f147057"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-23-2365-2023-ie00002.svg" width="90pt" height="17pt" src="acp-23-2365-2023-ie00002.png"/></svg:svg>. A positive feedback of sulfate on nitrate production was also observed in this work due to the shift in ammonia partitioning induced by the ALWC variation during haze aggravation. It implies the target controlling of haze should not simply focus on SO2 and NO2, but more attention should be paid to gaseous precursors (e.g., SO2, NO2, NH3) and aerosol chemical constitution during different haze stages.